Quality of Cauda Epididymal Spermatozoa of Ongole Crossbred Bull in Skim Milk, Tris, and Citrate Extenders Added with Egg Yolk - Solihati, N; Idi, R; Rasad, SD; Rizal, M; Fitriati, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The objective of this study was to find out the quality of cauda epididymal spermatozoa in skim milk, Tris, and citrate extenders added with egg yolk stored at 4-5oC. The study was laid out in a Completely Randomized Design (CRD) with three treatments and six replications. Evaluation of the quality of fresh spermatozoa was done after diluted with different extenders and stored at 4-5oC. The results showed that extenders have no significant effects (P>0.05) on motility, live sperms, abnormality, intact plasma membrane and viability of cauda epididymal spermatozoa stored at 4-5oC. It can be concluded that skim milk, citrate, and Tris extenders added with egg yolk have the same ability in maintaining the quality and viability of cauda epididymal sperms of Ongole crossbred bulls. (Animal Production 10(1): 22-29 (2008) Key Words: Ongol crossbred, spermatozoa, cauda epididymal, extenders